MYOFASCIAL INDUCTION IN CHRONIC LUMBOPELVIC PAIN. THREE CASES STUDY - Vela-Navacerrada, M (Cuestiones de Fisioterapia, 2010)
Introduction: myofascial induction is a method of working to relieve tension and to recover functional body balance. Objective: research on the evolution of three young women who have never given birth to a child with chronic lumbopelvic pain, subject to the same myofascial induction procedure to relieve tension in the spinal cord membrane. Patients and method: two of the cases have a trauma precedent and their work condition requires sitting about six hours. The other case has no precedent trauma, and she is a professional dancer. In all cases medullar damage was disregard and there was a previous treatment by means of other technichs (manipulative physiological therapy, electrotherapy), without having reached complete recovery. Results: symptoms relief is almost complete in all cases; the cases with more serious physical trauma or more permanent consequences require many more sessions than the others. Discussion/conclusions: myofascial induction is an appropriate method of working in these three cases of chronic lumbopelvic pain.